PERAN TAFSIR AL-MISBAH DALAM PENGEMBANGAN PEMAHAMAN KONTEKSTUAL AL-QUR'AN - Lukman Nurchakim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the importance of contextual understanding of the Qur'an in responding to the challenges of the modern era that continue to develop. The purpose of this study is to analyze the role of Tafsir Al-Misbah in developing contextual understanding of the Qur'an. The research method used is qualitative with a literature study approach, where data is collected from various relevant literature sources. The results of the study indicate that Tafsir Al-Misbah makes a significant contribution to enriching the contextual understanding of the Qur'an through a comprehensive and inclusive approach. The conclusion of this study is that Tafsir Al-Misbah plays an important role in developing contextual understanding of the Qur'an, so that it can help Muslims face various contemporary issues better.